AKASIA Program as an Environmentally Based Elderly Empowerment in the Anyelir 2 Harjamukti Farmers Group - Junita, Fanny Shinta; Devy Puspasari Siswaningrum; Nur Rahmi Fajri Yanti; Wendi Gustira (Prospect: Jurnal Pemberdayaan Masyarakat, 2025)
The increase in life expectancy in Indonesia has resulted in an increasing number of elderly people facing health, social, and quality of life challenges. On the other hand, environmental issues, particularly organic waste, are also a serious issue impacting society, including vulnerable groups such as the elderly. Given this complexity, interventions are needed that can address both issues in an integrated manner. This article discusses the AKASIA Program empowered elderly garden activity, a CSR initiative of PT Perusahaan Gas Negara Tbk - Cimanggis Station Offtake, implemented in collaboration with the Anyelir 2 Farmers Group in Harjamukti Village, Depok. This program uses a community empowerment approach through planning, implementation, and participatory monitoring and evaluation. Activities include urban farming training, organic waste processing, cultivation facilities, and ongoing mentoring. Results demonstrate that the program not only provides productive, social, and recreational space for seniors but also significantly improves their happiness, relaxation, and quality of life. Furthermore, the program contributes to reducing organic waste and opening up economic opportunities through the sale of agricultural products. Thus, the AKASIA Program demonstrates that senior empowerment can go hand in hand with environmental solutions and serves as a model for holistic and sustainable CSR collaboration at the community level.